(untitled) (Research, Society and Development, 2022)
This work is a compilation of some texts about how important mathematics modeling and mathematical games at teaching and learning these contents at elementary school. The goal is to analyse the positive influence of mathematical games and mathematical modeling like teaching tools. Therefore, we made a public policy analysis curriculum guide and of works already published, based on the exhibition of mathematical games as teaching strategies, as well as mathematical modeling being one of the methodological possibilities with the capacity of bringing down new contributions to the contextualized and effective teaching. We highligh some challenges at the educational process and the interference that mathematical games and mathemaical modeling exercise in this process. In these methodologies quoted, it’s possible to realize that a teacher can teach taking into account the reality of the students. We identify from reading and analysis of the studied documents how important is the conecction between school and Mathematics with the intent to prepare students for the society in which they live, contributing to the formation of responsible citizens being able to participate actively in the world permeated by science and technology.